Expanding Horizons, Evolving Through Time : FSSH 2018-2023 - Regina Garai, Abdullah; Kiky Kirina, Abdillah (UNIMAS Publisher, 2023)
This is a coffeetable book (ISBN 978-967-0054-56-8) about FSSH's activities and development from 2018 till 2023